The marvelous misadventures of Sebastian grand extravaganza, including a performance by the entire cast of the Gallimaufry-Theatricus. - Alexander, Lloyd (Dell Publishing, 1970)
When he loses his place as fourth fiddler in a noble household, Sebastian sets out into the world to seek his fortune.